Mortality in Catalonia during the summer of 2022 and its relation with high temperatures and COVID-19 cases - Coma, Ermengol; Pino, David; Mora, Núria; Fina, Francesc; Perramon, Aida; Prats, Clara; Medina, Manuel; Planella, Antoni; Mompart, Anna; Mendioroz, Jacobo; Cabezas, Carmen (Frontiers in Public Health, 2023)
Purpose To analyse the association between the mortality during the summer 2022 and either high temperatures or the COVID-19 wave with data from the Catalan Health Care System (7.8 million people). Methods We performed a retrospective study using publicly available data of meteorological variables, influenza-like illness (ILI) cases (including COVID-19) and deaths. The study comprises the summer months of the years 2021 and 2022. To compare the curves of mortality, ILI and temperature we calculated the z-score of each series. We assessed the observed lag between curves using the cross-correlation function. Finally, we calculated the correlation between the z-scores using the Pearson correlation coefficient (R2). Results During the study period, 33,967 deaths were reported in Catalonia (16,416 in the summer of 2021 and 17,551 in the summer of 2022). In 2022, the observed lag and the correlation between the z-scores of temperature and all-cause deaths was 3 days and R2 = 0.86, while between ILI and all-cause deaths was 22 days and R2 = 0.21. This high correlation between temperature and deaths increased up to 0.91 when we excluded those deaths reported as COVID-19 deaths, while the correlation between ILI and non-COVID-19 deaths decreased to −0.19. No correlation was observed between non-COVID deaths and temperature or ILI cases in 2021. Conclusion Our study suggests that the main cause of the increase in deaths during summer 2022 in Catalonia was the high temperatures and its duration. The contribution of the COVID-19 seems to be limited.